Pendidikan Karakter Berbasis Nilai-Nilai Aswaja - Yoyok Amirudin (VICRATINA, 2017)
This paper aims to find out about character education based on Aswaja values. There are 18 (eighteen) kinds of characters issued by the Ministry of Education. To make the character of students must have teaching behaviours that apply in the area. In this case, the majority of Indonesia has the ahlus sunnah wal jama’ah. So the Aswaja values should be implemented in schools. The values are tasamuh, tawazun, taadul and amar ma'ruf nahi munkar. These five values are not only owned by madrassas with a background of nahdliyin but schools under the auspices of the education office can implement these attitudes in order to produce students who have moral values. These attitudes can be practiced and implemented by students and teachers both in the learning process or outside of learning.Keywords: Character, Ahlusunnah wal jama’ah